An interdisciplinary and collaborative initiative in palliative care research - Veena Desa (Journal of Pain Research, 2008)
Veena Desa1, Cyril Danjoux2, Yvette Matyas1, Margaret Fitch3, Amna Husain4, Nina Horvath5, Jeff Myers5, Mark Clemons6, Janet E Hux5,7,8, Elizabeth A Barnes21Department of Administration; 2Department of Radiation Oncology; 3Psychosocial and Behavioral Research Unit, Toronto Sunnybrook Regional Cancer Centre; 4The Temmy Latner Centre for Palliative Care, Mount Sinai Hospital, Toronto, Ontario, Canada; 5Department of Family Medicine, Sunnybrook Hospital, Toronto, Ontario, Canada; 6Department of Medical Oncology, Toronto, Ontario, Canada; 7Institute for Clinical Evaluative Sciences, Toronto, Ontario, Canada; 8Department of Health Policy, Management, and Evaluation, University of Toronto, Toronto, Ontario, CanadaAbstract: The scale and complexity of palliative care increasingly demands that researchers move beyond their own discipline and explore interdisciplinary collaboration. At a Palliative Care Research Retreat held in January 2006 at the Toronto Sunnybrook Regional Cancer Centre, researchers from multiple care settings with the center and from other Toronto hospitals came together with the vision of becoming Canadian leaders in palliative care research. As a result of this retreat, five interdisciplinary groups were formed to pursue research in the areas of pain and symptom management, access to services, translational research, education, and communication. An overview of the retreat and direction of research for each group is provided.Keywords: palliative care, research retreat, pain and symptom management, access to care, translational research, palliative care education, communication